Role of entrepreneurial education, family background, attitude and self efficacy in determining students’ entrepreneurial intention: the moderation and mediation approach / Thominathan Santhanamery ... [et al.] - Santhanamery, Thominathan; Shafie, Dalili Izni; Song, Saw-Imm; Khalid, Nor Aminin (Universiti Teknologi MARA, 2023)
Entrepreneurship has been given thoughtful attention due to its importance in economic growth and job creation. Developing countries like Malaysia have encouraged students to be involved in entrepreneurship as their career choice to reduce the graduate unemployment level in the country. As a part of this effort, entrepreneurship subjects were made compulsory for all university students regardless of their field of study. Hence, understanding the factors that influence the engagement of these young minds in entrepreneurial endeavors holds significant importance. Thus, the main focus of this study is to explore how entrepreneurial education, family background, self-efficacy, and attitude influence the entrepreneurial intentions of undergraduate students. The sample consists of 429 UiTM students who have taken the entrepreneurship course. The data was analyzed using SPSS and Smart PLS 4.0. The findings revealed a significant relationship between students’ entrepreneurial education, family background, and attitude toward students’ entrepreneurial intentions. However, self-efficacy does not have a significant relationship with entrepreneurial intentions. The results also extracted that entrepreneurial attitudes moderate the relationship between entrepreneurial education, family background, and entrepreneurial intention. Nevertheless, no significant mediating effect was found between entrepreneurial education, family background, and self-efficacy concerning entrepreneurial intentions.